2020
DOI: 10.1021/acsbiomaterials.0c00035
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine Promotes Dentin Remineralization via Interfacial Control

Abstract: Biomineralization has intrigued researchers for decades. Although mineralization of type I collagen has been universally investigated, this process remains a great challenge due to the lack of mechanistic understanding of the roles of biomolecules. In our study, dentine was successfully repaired using the biomolecule polydopamine (PDA), and the remineralized dentine exhibited mechanical properties comparable to those of natural dentine. Detailed analyses of the collagen mineralization process facilitated by PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…According to our previous studies, we have established two rational mineralization solutions with different supersaturation with respect to HAP, according to the mineralization characteristics of reconstructed collagen fibers and dentinal collagen. 7,41 To achieve high mineralization efficiency in the different mineralized systems, we selected different polyelectrolytes, pAsp for collagen fibers and hydrogel mineralization, and PAA for dentin remineralization (see below), respectively. The mineralization of collagen fibers was performed in a mineralization solution, containing 1.67 mM CaCl 2 , 9.5 mM Na 2 HPO 4 , 150 mM NaCl, and 0.24 mg mL −1 pAsp ( M W = 9000–11 000).…”
Section: Methodsmentioning
confidence: 99%
“…According to our previous studies, we have established two rational mineralization solutions with different supersaturation with respect to HAP, according to the mineralization characteristics of reconstructed collagen fibers and dentinal collagen. 7,41 To achieve high mineralization efficiency in the different mineralized systems, we selected different polyelectrolytes, pAsp for collagen fibers and hydrogel mineralization, and PAA for dentin remineralization (see below), respectively. The mineralization of collagen fibers was performed in a mineralization solution, containing 1.67 mM CaCl 2 , 9.5 mM Na 2 HPO 4 , 150 mM NaCl, and 0.24 mg mL −1 pAsp ( M W = 9000–11 000).…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the adsorbed citrate molecules on collagen fibrils significantly reduced the interfacial energy between the collagen matrix and the ACP precursor via interface wetting effect, and therefore facilitating intrafibrillar mineralization of apatite at an early stage of biomineralization. Similarly, polydopamine (PDA) was utilized in their subsequent work by Qu et al [ 87 ] to promote dentin remineralization with decreased heterogeneous nucleation energy barrier by reducing interfacial energy of collagen/ACP.…”
Section: Intrafibrillar Mineralization Mechanismsmentioning
confidence: 99%
“…Over the last few years, mineralization systems based on ACP precursors have been further expanded. To promote the effects of dentin remineralization, several molecules, including L -glutamic acid, 181 aspartic acid, 182 glutaraldehyde, 183 citrate, 133 chondroitin sulfate 184 and polydopamine 185 have been introduced to accelerate the crystallization kinetics or facilitate the intrafibrillar penetration of the ACP precursor. For example, Tang et al 133 treated collagen fibrils with citrate and enhanced the wetting effect of ACP precursor towards collagen fibrils by remarkably reducing the interfacial energy between them (Fig.…”
Section: Dentin Remineralizationmentioning
confidence: 99%